Documental heritage in the focus of scientific literature: bibliometric study At Brapci – Base Of Journals In Information Science - Silva, Luiz Carlos da; Miguel, Marcelo Calderari; Costa, Rosa da Penha Ferreira da (Faculdade de Filosofia e Ciências, 2021)
Analyzing how the theme 'documentary heritage' appears in Information Science journals is the objective of this study. To identify contents in the scientific literature, bibliographic research is carried out in order to regain in the Referential Database of Articles of Journals in Information Science (BRAPCI) the documentary items on the theme. The study focuses on three parameters: i) To survey the published articles on documentary heritage in Information Science journals; ii) Check which journals are most representative for the archival area; iii) Describe the profile of the most productive authors in the analysis of documentary heritage according to their title and institution of origin. Since 1989, a database of 272 documentary items has been observed, of which 169 (62.13% of the total) fit the parameters established for carrying out this study, that is, the scientific articles from the period 2010 to 2020. Thus the research points to three magazines that publish the most on the researched theme: ‘Ágora - Arquivologia em Debate’, with 21 articles; the periodical ‘Em Questão’, with 13 items; and the ‘Informação & Informação’ magazine with nine publications respectively